Effect of dietary sodium on airways responsiveness and its importance in the epidemiology of asthma: an evaluation in three areas of northern England. Issue 9 (September 1995) - Devereux, G; Beach, J R; Bromly, C; Avery, A J; Ayatollahi, S M; Williams, S M; Stenton, S C; Bourke, S J; Hendrick, D J
Abstract : BACKGROUND--Although several investigations have shown a relationship between asthma (or its surrogate, airways responsiveness) and dietary or urinary sodium, others have not, and the matter remains controversial. This "salt effect" has been investigated during two recent epidemiological surveys of men in northern England. The first assessed the possible effect on airways responsiveness of occupational exposure to welding fumes, and the second characterised airways responsiveness in two geographically distinct residential areas. Thus, three separate study areas/populations were involved. METHODS--Investigation 1 involved 1059 shipyard workers aged 16-27 years who were exposed variously to welding fumes, and Investigation 2 involved 587 men aged 20-44 years who lived in rural West Cumbria or in urban Newcastle upon Tyne. In Investigation 1, a 24 hour urine specimen was requested from each subject with quantifiable airways responsiveness (PD20 < or = 6400 micrograms methacholine) and from an equal number of subjects without measurable airways responsiveness from the same occupational subgroup. In Investigation 2, every subject was asked to provide a 24 hour urine specimen. RESULTS--Of the men undergoing methacholine tests, satisfactory 24 hour urine specimens were obtained from 234 (22.1%) in Investigation 1 and 232 (39.5%) in Investigation 2. Analysis using multiple linear regression, multiple linear logistic regression, and multiple regression for censored data produced consistent results within each study population but conflicting results between them, such that there was no hint of a relationship between airways responsiveness and 24 hour urinary sodium excretion in the shipyard workers of Investigation 1 nor in the rural West Cumbrian population of Investigation 2, but an association was found in the urban Newcastle population of Investigation 2. All study populations were sufficiently large to demonstrate anticipated relationships between airways responsiveness and atopy, baseline FEV1, and (Newcastle only) age. CONCLUSIONS--If airways responsiveness is related to dietary sodium the relationship is not likely to be strong.